Architectures of Fire - Gheorghiu, Dragos (Archaeopress, 2019)
Papers presented here originate from a session held during the 2015 Annual Meeting of the European Association of Archaeologists (Glasgow). The contributors attempt to present the entanglement between the physical phenomenon of fire, the pyro-technological instrument that it is, its material supports, and the human being.